Comparative analysis of static and dynamic performance of nonpneumatic tire with flexible spoke structure - Zhang, Zifeng (Strojniški vestnik, 2020)
Based on ABAQUS software, the three-dimensional finite element models of 195/50R16 radial tire and three kinds of nonpneumatic tire, i.e., spoke plate, honeycomb and grid type, are established, and the static and dynamic performance of the four finite element models of tire are analysed. The results show that in the static condition analysis, the ground pressure of the nonpneumatic tire is distributed on both sides of the tread; the stress concentration of the nonpneumatic tire mainly occurs in the grounding area near the support spoke; the deformation area of nonpneumatic tire mainly appears in the area of grounding and adjacent to the grounding spoke; In the analysis of the tire's steady rolling condition, the ground imprint of a nonpneumatic tire is similar to that of a bar rectangle, and the ground pressure distribution is relatively uniform. The static and dynamic characteristics of honeycomb nonpneumatic tire are close to that of a radial tire. The research work of this paper will provide some reference for the structural design and parameter optimization of nonpneumatic tires.
Keywords: analiza napetosti; analiza po metodi končnih elementov ABAQUS; dinamične lastnosti; dynamic characteristics; ground pressure distribution; load-carrying characteristics; nepnevmatsko kolo; nonpneumatic tire; nosilnost; porazdelitev pritiska na podlago